2002
DOI: 10.1523/jneurosci.22-15-06437.2002
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of a Lysosomal Enzyme in the Adult Brain by Axonal Transport and by Cells of the Rostral Migratory Stream

Abstract: A portion of the lysosomal enzymes produced by cells is secreted, diffuses through extracellular spaces, and can be taken up by distal cells via mannose-6-phosphate receptor-mediated endocytosis. This provides the basis for treating lysosomal storage diseases, many of which affect the CNS. Normal enzyme secreted from a cluster of genetically corrected cells has been shown to reverse storage lesions in a zone of surrounding brain tissue in mouse disease models. However, low levels of enzyme activity and reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 70 publications
8
94
0
Order By: Relevance
“…As has been observed with AAV2 vectors expressing other transgenes, 28,29 we observed a high level of TPP-I expression in cell populations not directly at the site of injection, but whose axonal projections were located in the site of the injection. As widespread delivery of the gene product throughout the brain is a goal of the current study, we examined other brain regions that project to the striatum to determine if expression of TPP-I could be detected in projection neuronal populations following single intrastriatal administration of AAV2 CU hCLN2.…”
Section: Aav-mediated Cns Transfer Of Cln2 D Sondhi Et Alsupporting
confidence: 85%
“…As has been observed with AAV2 vectors expressing other transgenes, 28,29 we observed a high level of TPP-I expression in cell populations not directly at the site of injection, but whose axonal projections were located in the site of the injection. As widespread delivery of the gene product throughout the brain is a goal of the current study, we examined other brain regions that project to the striatum to determine if expression of TPP-I could be detected in projection neuronal populations following single intrastriatal administration of AAV2 CU hCLN2.…”
Section: Aav-mediated Cns Transfer Of Cln2 D Sondhi Et Alsupporting
confidence: 85%
“…We have also observed this in mice where it has been shown that episomal forms of vector DNA persist in brain tissue, therefore, small amounts of sense riboprobe may have hybridized to the nontranscribed strand of the episomal DNA. 3,42 No evidence of hybridization was seen in regions of uninjected brain using either the sense or antisense riboprobe.…”
Section: Aav In the Cat Brain Ch Vite Et Almentioning
confidence: 99%
“…21 No evidence of retro-or anterograde transport in the cat brain was found with any of the three serotypes used. Although axonal transport of a lysosomal enzyme has been reported in the mouse, 42 there are several possible explanations for this apparent difference. First, the regions of the brain in which transport was examined in the mouse, the intrahippocampal and septohippocampal pathways, were not tested in the cat so a direct comparison is not possible.…”
Section: Aav In the Cat Brain Ch Vite Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…While prior work with AAV type 2 (AAV2) vectors showed poor NPC transduction following direct SVZ injection, AAV2 did successfully transduce human NPCs in vitro. 9,10 We previously showed that AAVs possessing different capsid structures have altered tropism when introduced into the mammalian brain. 11 For example, AAV4 transduced ependyma with high efficiency when injected into the striata or lateral ventricles of adult mice.…”
Section: Introductionmentioning
confidence: 99%